2022
DOI: 10.1111/epi.17342
|View full text |Cite
|
Sign up to set email alerts
|

Consequences: Bench to home

Abstract: Seizure clusters (also referred to as acute repetitive seizures) consist of several seizures interspersed with brief interictal periods. Seizure clusters can break down γ‐aminobutyric acidergic (GABAergic) inhibition of dentate granule cells, leading to hyperactivation. Functional changes to GABAA receptors, which play a vital neuroinhibitory role, can include altered GABAA receptor subunit trafficking and cellular localization, intracellular chloride accumulation, and dysregulation of proteins critical to chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…Figures 7C , 8C show hotspots , such as “dentate gyrus,” “glioma,” “GABA,” “AE,” “GAD,” “activation,” “mutation,” “glia,” “lamotrigine,” and “zonisamide.” For many years, the dentate gyrus has been the focal point of research on the molecular, cellular, and network mechanisms that underlie epileptogenesis in TLE ( Dudek and Sutula, 2007 ). Two hypothesized mechanisms have received particular interest and experimental support: (1) selective loss of vulnerable interneurons within the hilus region and (2) the establishment of new recurrent excitatory circuits after sprouting mossy fibers ( Kapur et al, 2022 ; Ramos et al, 2022 ). Tumor-associated epilepsy and gliomas share pathophysiological mechanisms contributing to ictogenesis and tumor progression ( Huberfeld and Vecht, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 7C , 8C show hotspots , such as “dentate gyrus,” “glioma,” “GABA,” “AE,” “GAD,” “activation,” “mutation,” “glia,” “lamotrigine,” and “zonisamide.” For many years, the dentate gyrus has been the focal point of research on the molecular, cellular, and network mechanisms that underlie epileptogenesis in TLE ( Dudek and Sutula, 2007 ). Two hypothesized mechanisms have received particular interest and experimental support: (1) selective loss of vulnerable interneurons within the hilus region and (2) the establishment of new recurrent excitatory circuits after sprouting mossy fibers ( Kapur et al, 2022 ; Ramos et al, 2022 ). Tumor-associated epilepsy and gliomas share pathophysiological mechanisms contributing to ictogenesis and tumor progression ( Huberfeld and Vecht, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…(1) selective loss of vulnerable interneurons within the hilus region and (2) the establishment of new recurrent excitatory circuits after sprouting mossy fibers (Kapur et al, 2022;Ramos et al, 2022). Tumor-associated epilepsy and gliomas share pathophysiological mechanisms contributing to ictogenesis and tumor progression (Huberfeld and Vecht, 2016).…”
Section: Figure 4dmentioning
confidence: 99%
“…Rescue therapy is a critical component of seizure cluster management, both to reduce the risks of prolonged seizures and to prevent the progression to status epilepticus 1–3 . Moreover, effective rescue therapy is important to reduce the need for emergency services as well as the clinical and quality‐of‐life burdens of seizure clusters for patients, family members, and caregivers/care partners (please see Kapur et al, Consequences: Bench to Home 4 for further discussion on the impact of seizure clusters). Ideal rescue therapies should be easy and safe to administer, be effective at small doses (with a large therapeutic index), and exhibit rapid onset of action that can be sustained for several hours 5 …”
Section: Introductionmentioning
confidence: 99%
“…Others have suggested that the use of educational and quality‐of‐life measurements could be more appropriate 12 . More details regarding the impact of seizure clusters on patient and caregiver quality of life are discussed by Kapur et al in Consequences: Bench to Home in this supplement 13 . One study looked at health care utilization outcomes and scores on the Modified Impact on Families (MIF) questionnaire at 3 and 12 months in 54 patients with epilepsy who received an SAP and 48 patients who had standard care alone 14 .…”
Section: Introductionmentioning
confidence: 99%
“…12 More details regarding the impact of seizure clusters on patient and caregiver quality of life are discussed by Kapur et al in Consequences: Bench to Home in this supplement. 13 One study looked at health care utilization outcomes and scores on the Modified Impact on Families (MIF) questionnaire at 3 and 12 months in 54 patients with epilepsy who received an SAP and 48 patients who had standard care alone. 14 Differences in health care utilization were not seen between the groups; however, among patients with ≤12 seizures per year, seizure comfort scores on the MIF questionnaire at 12 months were significantly higher in the SAP group compared with the standard care group.…”
Section: Introductionmentioning
confidence: 99%